A Phenomenology of SNS Sharing - Wittkower, D.E. (AoIR Selected Papers of Internet Research, 2013)
In this contribution to a phenomenology of social network sites (SNS), we see how the share button brings about an alteration in our being-with others. On the side of the sharer, we see an experience of the world in a mode of possible retroactive sociality, creating an enigma in the constitution and attention of the subject of a given experience. On the side of the receiver, we see how being shared with creates sometimes unwelcome retrospective ideation of the sharer’s experience, and requires a choice whether, by liking or commenting, to bring the sharer into retroactive awareness of having been experiencing the shared alongside the receiver. Only if and when the shared has been received and the reception has been shared is asynchronous being-with at a distance constituted.